Philosophical Poetry as a Form of Memory. On a Poem by Hannah Arendt - Oxana A. Koval; Ekaterina B. Kriukova (Studia Litterarum)
Hannah Arendt’s intellectual legacy includes a collection of poems that have not received much attention from scholars. Arendt began writing these poems in her youth and continued into adulthood. Her American period of poetry reflects on the experience of emigration and the loss of loved ones. The collection begins with a poem dedicated to the death of her friend, the philosopher Walter Benjamin. The lyrical necrology, entitled with the initials “W.B.” and dated 1942, is both a tribute to the dead thinker and a reaction to the first reports of German death camps. This article reconstructs the origins of the poem and provides a detailed analysis of it. The interpretation is based on clarifying the philosophical subtext of this work, which deals with themes important to Arendt and Benjamin. For this purpose, the article uses such Arendt’s writings as the essay “We Refugees” (1943), the lecture “Walter Benjamin” (1968), and the book “The Life of the Mind” (1978). The example of the poem demonstrates the continuity and consonance of Arendt’s ideas with Benjaminian concepts of aura (“The Work of Art in the Age of Mechanical Reproduction”), Jetztzeit (“On the Concept of History”), and remembrance (“Berlin Childhood Around 1900”).